Within-Population Trait Variation in a Globally Invasive Plant Species Mayweed Chamomile (Anthemis cotula): Implications for Future Invasion and Management - Adhikari, Subodh; Burke, Ian C.; Revolinski, Samuel R.; Piaskowski, Julia; Eigenbrode, Sanford D. (Frontiers in Agronomy, 2021)
Quantification of variation for phenotypic traits within and among weed populations facilitate understanding of invasion mechanisms and management tactics. In the Pacific Northwest (PNW), USA, in response to climate change and to improve sustainability, producers are increasingly adopting broadleaf crops and cover crops, but Mayweed chamomile (Anthemis cotula L.) is a significant barrier to diversifying cropping systems because of its abundance and lack of herbicide options for its control. To quantify within-population phenotypic trait variation and heritability, plants (n = 300) from six half-sib families (i.e., seed source plants or mother plants) from each of ten A. cotula populations (infested farms or sites) in the PNW were grown from seed through the flowering stage in the greenhouse common garden experiment. We measured percent seedling emergence, the initial date of flowering, flowering duration, plant biomass, number of flower heads, floral scent profiles, and other traits on individual plants. Trait variation was high among half-sib families within each population. For example, in two of the populations, percent seedling emergence within 30 days of planting ranged from 5% to 41% and 3% to 53%, respectively. As another example, initial date of flowering in two other populations ranged from 61 to 93 days and 58 to 92 days, repectively. Differences among half-sib families were greatest for flowering period, which differed by a month in most populations, and floral scent profiles. Heritability estimates were higher than 1.0 for most phenotypic traits, indicating that the study plants shared their ancestors more (i.e., full-sibs or product of selfing) than just being half-sibs. These patterns of phenotypic trait variation are potentially caused by local edaphoclimatic factors and within-field farm management practices, suggesting that management of A. cotula might be challenging and differ within and across farms.